Inovasi Pendidikan di Masa Pandemi Covid-19 - Ansori, Aan; Sari, Ahmad Fitriyadi (Jurnal Literasi Pendidikan Nusantara, 2020)
This paper was written with the aim of explaining the meaning of education, educational innovation, educational policy, the Covid-19 pandemic. The writing method uses Microsoft Word and journal templates. Mendeley's app is used for citation and APA 7th (American Psychological Association 7th edition) as reference style. The data for the discussion of papers are obtained from primary and secondary data from books and journals of international and national reputation. The results of writing a paper show that educational innovation includes new changes, to increase the ability to achieve educational goals. Which includes technology, human resources and government policies.These three things hold an important role that must be collaborative, they cannot work independently, a synergity was required to build education.